Impact of the COVID-19 pandemic on breast cancer screening and early diagnosis - Erilaine de Freitas Corpes; Kauane Matias Leite; Denise Montenegro da Silva; Ana Cínthia Silva Alves; Régia Christina Moura Barbosa Castro; Andrea Bezerra Rodrigues (Universidade Federal do Ceará, 2022)
Objective: to analyze the impacts of the COVID-19 pandemic on breast cancer screening and early diagnosis. Methods: an ecological retrospective study of data from the Department of Informatics of the Unified Health System collected between 2016 and 2020 was carried out. The data collection was guided by a semi-structured script, and the impact of the pandemic on breast cancer screen and diagnosis was established by using a formula and comparing the period of interest to 2020. Results: in Brazil, there was a significant drop in mammograms performed during the COVID-19 pandemic, with a decrease of 361,855 exams from 2016 to 2020. Most diagnostic investigations were conducted with patients between 50 and 59 years, and there was a significant drop in mammograms in women aged under 40 years. Conclusion: the COVID-19 pandemic has negatively impacted screening and early diagnosis of breast cancer due to reduced availability. Contributions to practice: the study reinforces the importance of investing in public policies to face the pandemic scenario so that screening and treatment protocols be well targeted to guarantee better care for cancer patients.